On the relationship of morphology evolution and thermal conductivity of flax reinforced polypropylene laminates - Bodaghi, Masoud; Delfrari, Doriane; Lucas, Margot; Senoussaoui, Noha-Lys; Koutsawa, Yao; Uğural, Burcu Karaca; Perrin, Henri (Frontiers in Materials, 2023)
This paper focuses on the morphology evolution in the forming process of unidirectional flax reinforced polypropylene composite laminates. The link between the morphology evolution and thermal conductivity during consolidation stages is investigated. Hot press forming allows to manufacture several composite laminates at different consolidation stages as a function of the compaction thickness. Microscopic evolution of the laminates in terms of morphology and porosity fractions are evaluated by scanning electron microscopy and X-ray microtomography (µ-CT). Hot disk technique is applied to measure the thermal conductivity of the laminates in in-plane and transverse directions. It is found that the in-plane thermal conductivity almost linearly increases with the reduction of porosity fraction. However, the transverse thermal conductivity remained constant. Beside the proposed relations, a theoretical model, based on a two-level Mori-Tanaka homogenization method is proposed. Considering the three-phases material (i.e., porosity, fiber, and polymer matrix), there is a good agreement between the experiment data and model predictions, but limited predictivity for porosity level above 15% certainly due to simplifying assumptions used in the predictive model.